2019
DOI: 10.1002/slct.201903254
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)‐Catalyzed Azide‐Alkyne Cycloaddition Microwave‐Assisted: Preparation of 7‐(4‐Substituted‐1H‐1,2,3‐Triazol‐1‐yl)‐Fluoroquinolones

Abstract: Nowadays, the pharmaceutical industry faces the challenge of innovating and increasing the productivity of new medicines due to the increasing multidrug resistance among bacteria, viruses and fungi. The main objective of the present study is connected quinolone and triazole molecules to enhance and broad antibacterial spectrum as well as to have multiple mechanisms of action. Preparation of 4‐substituted‐1H‐1,2,3‐triazol‐1‐yl in C‐7 of 6‐fluoro‐ and 6,8‐difluoro‐quinolone ring is showed. The synthesis involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Reducing an azide group at the C‐7 position [42–44] can also produce amine moieties. Azides are essential intermediates in medicinal chemistry, enabling the synthesis of heterocycles such as triazoles and tetrazoles, allowing quinolone‐triazole or tetrazole hybrids to be generated [45–48] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing an azide group at the C‐7 position [42–44] can also produce amine moieties. Azides are essential intermediates in medicinal chemistry, enabling the synthesis of heterocycles such as triazoles and tetrazoles, allowing quinolone‐triazole or tetrazole hybrids to be generated [45–48] …”
Section: Resultsmentioning
confidence: 99%
“…Azides are essential intermediates in medicinal chemistry, enabling the synthesis of heterocycles such as triazoles and tetrazoles, allowing quinolone-triazole or tetrazole hybrids to be generated. [45][46][47][48] Another successful route to 7-amino-fluoroquinolones uses p-methoxybenzyl amine (PMBA), notably achieving good yields under mild conditions. [49][50][51] In this method, nucleophilic aromatic substitution (S N A) occurs, forming the NÀ C bond between the PMBA and the fluoroquinolone ring, and subsequent hydrolysis of p-methoxybenzyl moiety under acid conditions yields 7-amino-fluoroquinolones.…”
Section: Synthesis Of Fluoroquinolonesmentioning
confidence: 99%
“…In these protocols, propargyl substituted indoline ( 1 a ) or coumarin ( 1 b ) were employed in the presence of Cu(I) iodide as catalyst [7a–c] . Apart from CuI, Cu(II) sulphate has also been reported for these reactions under microwave‐irradiation in presence of sodium ascorbate for coumarin ( 1 b ) or quinoline ( 2 c ) based scaffolds [7c,d] . The strategy has also been employed for the synthesis of some imidazolo‐1,2,3‐triazole hybrids as antioxidant and antimicrobial agents [7e] .…”
Section: Microwave‐assisted Chemistry Of Poly‐aza‐heterocyclesmentioning
confidence: 99%
“…The authors have concluded that the use of microwave irradiation has dramatically reduced the reaction time to 10 min with great improvements in the yields, Scheme 11. A microwave-assisted protocol for the synthesis of 7-triazol-1-yl-fluoroquinolone using copper(II) sulfate (CuSO 4 ) as catalyst for the azide-alkyne cycloaddition has been proposed by Cardoso-Ortiz and coworkers [34]. Two reaction procedures were employed, one under conventional heating, while the other one performed under microwave irradiation.…”
Section: Azide-alkyne Huisgen [2 + 3] Cycloaddition Reactionmentioning
confidence: 99%